Interelasi Teori Evolusi Manusia dan Tafsir Al-Mishbah: Pemahaman Mendalam tentang Penciptaan Manusia - Awaluddin, Raisa Zuhra Salsabila; Zuhri, Ahmad; Rambe, Uqbatul Khoir (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Interrelation of Human Evolution Theory and Al-Mishbah Interpretation: In-depth Insights into the Creation of HumanityThis study explores the concept of human creation in the Qur'an and the widely discussed human evolution theory. It addresses the interpretation of human creation according to Quraish Shihab and the interrelation between Quraish Shihab's interpretation and evolutionary theory, leading to the emergence of connections between evolutionary theory and Al-Mishbah interpretation, which can be explored by interpreters. Building upon these issues, the study reveals that evolutionary theory not only explains human evolution but is also related to all living beings in nature. Unlike Darwin's theory, which suggests that humans originated from apes, this study emphasizes the correlation between human evolution theory and Al-Mishbah's interpretation of human creation, both for the first human and subsequent generations. This is evident in the Qur'an's depiction of human creation after Prophet Adam, detailing the inevitable changes from infancy to old age. Human evolution is closely linked to the Qur'an, contrasting with Darwinian evolution, as the Qur'an specifies the origin of humans, as interpreted by Quraish Shihab. The research employs a literature review methodology, drawing data from relevant sources